2016
DOI: 10.1016/j.kint.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the thioredoxin-interacting protein (TXNIP) gene by hyperglycemia in kidney

Abstract: Diabetic kidney disease is the leading cause of end-stage renal disease. Genetic factors have been suggested to contribute to its susceptibility. However, results from genetic studies are disappointing possibly because the role of glucose in diabetic kidney disease predisposed by epigenetic mechanisms has not been taken into account. Since thioredoxin-interacting protein (TXNIP) has been shown to play an important role in the pathogenesis of diabetic kidney disease, we tested whether glucose could induce expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 34 publications
2
48
1
Order By: Relevance
“…; Zhong & Kowluru, ; De Marinis et al . ). One of the hallmarks of diabetic nephropathy and of a variety of chronic kidney diseases is the accelerated synthesis of extracellular matrix leading to tubulointerstitial fibrosis.…”
Section: Discovery and Domain Organization Of Myocardin Family Coactimentioning
confidence: 97%
“…; Zhong & Kowluru, ; De Marinis et al . ). One of the hallmarks of diabetic nephropathy and of a variety of chronic kidney diseases is the accelerated synthesis of extracellular matrix leading to tubulointerstitial fibrosis.…”
Section: Discovery and Domain Organization Of Myocardin Family Coactimentioning
confidence: 97%
“…Although it is not clear if HAT gene expression and activity is affected by diabetes state in pancreatic islets, previous studies in other tissues have shown that HAT activity and histone acetylation is increased in kidneys of diabetic mice (Wang et al, 2015;Cai et al, 2016;De Marinis et al, 2016), as well as increased p300 gene expression in diabetic rat heart (Aziz et al, 2013). Inhibition of p300 by chemical inhibitor curcumin has been shown to prevent renal damage and dysfunction in streptozotocin (STZ)-induced diabetic mice (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, novel curcumin analogs and derivatives have been identified for their potential use as anti-diabetic agents (i.e., for kidney disease). In particular, the curcumin analog C66 has been shown to mitigate diabetic nephropathy in diabetic mice through the suppression of c-Jun N-terminal kinase (JNK) activation, p300/CBP expression and total HAT activity (96). In another study examining the epigenetic effects of glucose on the expression of the proinflammatory gene, thioredoxininteracting protein (TXNIP), in diabetic Sur1-E1506K +/+ mice, it was discovered that the p300 inhibitor C646 reverses histone acetylation and consequently, represses hyperglycemiastimulated TXNIP expression (97) (Figure 3B).…”
Section: Curcumin and Its Analogsmentioning
confidence: 99%